Acoustically Levitated Sample Introduction for GC-MS: A Novel Contactless Approach to Direct Volatile Analysis - Akkaya, Erhan; Koyuncu, Ikbal (WILEY, 2025)
Conventional GC-MS sample introduction methods often involve physical contact, increasing contamination risk and analyte degradation, especially in sensitive matrices. This study introduces a novel, contactless interface using standing-wave acoustic levitation to suspend analytes in mid-air prior to GC-MS analysis. A 28 kHz ultrasonic transducer, powered by a high-voltage amplifier, generates stable levitation nodes inside a custom chamber, enabling droplets and solid particles to remain airborne during volatilization. Volatile analytes are transferred via heated gas mixture directly into the GC inlet. Acetone droplets yielded strong, reproducible m/z 58 ion signals, and real samples like cucumber (Cucumis sativus) skin demonstrated broader applicability. Helium-nitrogen gas mixture was optimized for both levitation stability and ionization efficiency. The system minimized surface contact, preserved sample morphology, and reduced cross-contamination risks. This platform establishes acoustic levitation as a viable sample delivery strategy for GC-MS, offering enhanced cleanliness, reduced sample loss, and novel handling of delicate or trace-level materials. It opens new directions for automation and integration in analytical workflows.
Keywords: acoustic levitation; contactless sampling; GC-MS; ultrasonic transducer; volatile analysis; Biochemistry & Molecular Biology; Chemistry; Spectroscopy